(untitled) (Research, Society and Development, 2022)
Environmental Accounting is an internal management tool that has the purpose of highlighting environmental costs, expenses and revenues to subsidize business decision-making. And due to the potential of this tool that can contribute to the preservation of natural resources, this study proposed, as a general objective, to describe through a model how to implement environmental accounting in a dairy industry. For this, an exploratory and descriptive research was carried out, with a qualitative approach of the case study type, in a dairy industry located in the city of Três Corações - MG. The company administrator and the production technician were interviewed. Through their reports, it was possible to apply and identify whether the company met each stage of the proposed model for the implementation of Environmental Accounting. In the case of non-attendance, recommendations were proposed by the researchers. In the end, it was found that this dairy has financial availability to make investments in the environmental sphere and that it has the potential to develop and implement environmental accounting.